PLACING CULTURE IN ENGLISH LANGUAGE TEACHING: THE INDONESIAN EFL STUDENTS’ PERCEPTION - Aksendro Maximilian (JETA (Journal of English Teaching and Applied Linguistic), 2021)
This research article presents the study about the EFL students’ perception on placing culture in ELT practice, especially in Indonesia context. The purpose of this survey study is to examine students’ perception on the integration of culture into ELT practice. The participants were the third-semester students in Mathematics Education Study Program, STKIP PGRI Bandar Lampung (Institute of Teachers Training and Education of PGRI Bandar Lampung), Indonesia. The data was collected using a questionnaire which was posted for the students who were taking the compulsory English subject. It is found that tertiary level students in Indonesia have realized the necessity and importance of placing culture in learning English. One of the importance is that placing culture into English classes could encourage students’ interest and motivation in learning English. The students also agree that their English language skills, speaking, writing, reading and listening, influenced by the existence of cultural content in their learning activities could be improved. Consequently, the culture-based materials are suggested to be developed.